2019
DOI: 10.1167/iovs.18-25883
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Exercise in Mice Is Sufficient to Protect Retinal Function During Light-Induced Retinal Degeneration

Abstract: Purpose We previously reported that a specific treadmill running exercise regimen protects against light-induced retinal degeneration (LIRD) in mice. We hypothesized that this protective effect varies with running intensity. To test this, mice undergoing LIRD were run at different treadmill speeds and retinal function was assessed. Methods BALB/c mice were assigned to LIRD groups at varying treadmill speeds—0, 5, 10, or 20 m/min labeled inactive, low, medium, and high, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…38,39 Our work, as well as others, has shown that increases in corticosterone and activation of the MAPK pathway, as well as CREB, can elicit neuroprotective pathways and protect from lightinduced retinopathy. 32,[40][41][42] In addition to activating a stress response, early weaning can delay the triggering of satiety and modulate the circadian rhythm of food intake, which was demonstrated in male Wistar rat pups out to PD100. 43 It is feasible that changes in behavioral satiety and food consumption can impact the retina, because recent studies have linked the gut microbiota with retinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Our work, as well as others, has shown that increases in corticosterone and activation of the MAPK pathway, as well as CREB, can elicit neuroprotective pathways and protect from lightinduced retinopathy. 32,[40][41][42] In addition to activating a stress response, early weaning can delay the triggering of satiety and modulate the circadian rhythm of food intake, which was demonstrated in male Wistar rat pups out to PD100. 43 It is feasible that changes in behavioral satiety and food consumption can impact the retina, because recent studies have linked the gut microbiota with retinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal functions of control (n=16 for Gad2-Cre and vGAT-Cre ) and DTA+FLP (n=24 for Gad2-Cre and vGAT-Cre ) mice were measured with a commercial ERG system (RetiMINER, China). After overnight dark adaptation [61], the mice were anesthetized by intraperitoneally injecting ketamine and xylazine (60 mg/kg and 16 mg/kg bodyweight, respectively), and then lightly secured to a stage with fastener strips across the back to ensure a stable, reproducible position for ERG recordings. All procedures were performed under dim red light.…”
Section: Methodsmentioning
confidence: 99%
“…Electroretinography. We tested retinal function using full-field flash electroretinography (ERG) as previously described (Mees et al, 2019). Briefly, after overnight dark-adaptation, we anesthetized mice (ketamine 60 mg/kg/, xylazine 7.5 mg/kg) under dim red light, anesthetized corneas with tetracaine (0.5%; Alcon) and dilated pupils with tropicamide (1%; Sandoz).…”
Section: Visual Stimulimentioning
confidence: 99%
“…Mean ± SEM is plotted throughout the figure. See (Mees et al, 2019) for detailed description of ERG Methods.…”
Section: Diminished Cortical Excitation During Perceptual Impairmentsmentioning
confidence: 99%